S42 Sex differences in reported quality of life in bronchiectasis: an analysis of the embarc registry. (15th November 2017) - Finch, SM; Shoemark, A; Crichton, M; Loebinger, M; Polverino, E; Aliberti, S; Goeminne, P; Vendrell, M; Soyza, A De; Dimakou, K; Chalmers, JD
Abstract : Introduction: Bronchiectasis is a chronic disease with a major impact on Quality of Life (QoL). As part of the EMBARC European Bronchiectasis Registry patients complete a Quality of Life-Bronchiectasis (QoL-B) questionnaire annually. The QoL-B has been validated and is widely used to give a comprehensive picture of the QoL across different aspects of patient's lives. Bronchiectasis is more common in females but sex differences in disease impact have not been explored. Methods: The EMBARC registry is a prospective observational study of adult patients with clinically significant bronchiectasis from 27 European countries. Baseline QoL-B questionnaires were analysed cross-sectionally using multiple linear regression to identify independent determinants of QoL across the 8 domains. Results: 8389 patients were included, 58% were female, median age 68 years. Men and women appear to have a similar level of disease severity with no significant differences in the Respiratory Symptoms, Role Functioning and Health Perception domains of the QoL-B. There was however a significant difference in all other aspects of the QoL scores. Male patients had higher scores for Physical functioning, with β coefficient 4.9 (95% CI 3.3–6.5, p<0.0001) (indicating an average of 4.9 points higher for men when adjusted for confounding variables). Men also had higher scores for Emotional Functioning (β coefficient 3.6 (95%CI 2.2–5.1), p<0.0001), Social Functioning (β coefficient 2.4 (95% CI 0.7–4.1), p=0.007) and Vitality (β coefficient 2.5 (95%CI 1.2–3.9), p<0.0001). Across all domains, the elements with a large effect were Breathlessness, Comorbidities (with Depression and Anxiety commonly having a large impact), Pseudomonas aeruginosa infection and frequent exacerbations. Female patients nevertheless had greater disease impact even after adjusting for these variables. Conclusions: From this large dataset we show that despite similar levels of disease severity, women living with bronchiectasis are significantly more affected in physical, emotional and social functioning aspects of their lives than their male counterparts. This has implications for tailoring care and suggests a need for more holistic care for patients with bronchiectasis.